KEANEKARAGAMAN HEWAN TANAH SEBAGAI BIOINDIKATOR KUALITAS TANAH DI LAHAN TEBU PUPUK ORGANIK DAN LAHAN TEBU PUPUK NON ORGANIK DESA WONOKUSUMO KECAMATAN TAPEN KABUPATEN BONDOWOSO - Miftahul Afifatur (Gunung Djati Conference Series, 2021)
Species diversity is a community level characteristic based on species abundance that can be used to express community structure. Soil fauna can be used as a parameter of soil quality. Environmental quality greatly affects the diversity of soil animals. One of them is when the sugarcane fields are fertilized with organic fertilizers and non-organic fertilizers. These conditions have a different effect on the diversity of soil animals on each land. This observation was carried out by observing soil animals in sugarcane fields with organic fertilizers and sugarcane fields with non-organic fertilizers in Wonokusumo Village, Tapen District, Bondowoso Regency on May 1 and 2, 2021 at 09.00 WIB. The method used is the hand sorted method, which is looking for animals by hand on the soil that has been taken from a certain depth. The depth used is 20 cm. Organic and non-organic environments have different effects on the diversity of soil animals caused by various factors. Therefore, this observation is important to carry out in order to know the diversity of soil animals in sugarcane fields with organic and non-organic fertilizers in Wonokusumo Village, Tapen District, Bondowoso Regency and can be used for ecological purposes. The results showed that the diversity of soil animals in sugarcane fields with organic fertilizers had a moderate level of diversity, while those in sugarcane fields with non-organic fertilizers had low levels of diversity.